Medicinal plants from brazilian cerrado biome: Potential sources of new anti-inflammatory compounds and antitumor agents on ehrlich carcinoma - Malara, Fábio de Andrade [UNESP]; Matos, Djamile C. [UNESP]; Ribeiro, Lívia C.A. [UNESP]; Falcoski, Thais O.R. [UNESP]; Andrade, Teresinha J.A.S. [UNESP]; Santos, Vanessa N.C.; Lima, Nerilson M.; Carlos, Iracilda Z. [UNESP] (FapUNIFESP (SciELO), 2021)
This work describes a pharmacological screening of Brazilian medicinal plants through their anti-inflammatory and cytotoxicity activities. Cytotoxicity activity of Mouriri elliptica and Alchornea glandulosa as well as the drugs celecoxib and doxorubicin were evaluated in cultures of peritoneal macrophages. The immune system influence of these samples was analyzed by determining production/inhibition of NO, production of tumor necrosis factor-α and production of interleukin-10. Regarding the production/inhibition of NO, there was NO production by M. elliptica and NO inhibition when the cells were exposed to A. glandulosa; Macrophages generally produce more NO, plus TNF-α and less IL-10, when associated to the tumor phenomenon, characterizing the inflammation involved in cancer. A. glandulosa showed anti-inflammatory effect, inhibited NO production and it was associated with low TNF-α production, although not as low as the macrophages associated with celecoxib and doxorubicin. These cytokines were not different in animals with tumor. Celecoxib confirms its anti-inflammatory action by markedly inhibiting NO and TNF-α, but also inhibiting IL-10 which is an anti-inflammatory cytokine. Doxorubicin inhibited NO in a higher percentage in the group of animals with tumor, although the literature reports that this drug stimulates the production of NO and this collaborates with its cytotoxic effect.
Keywords: Alchornea glandulosa; Anti-inflammatory; Cytotoxicity; Ehrlich carcinoma; Mouriri elliptica